2002
DOI: 10.1385/mn:26:1:097
|View full text |Cite
|
Sign up to set email alerts
|

Secretin as a Neuropeptide

Abstract: The role of secretin as a classical hormone in the gastrointestinal system is well-established. The recent debate on the use of secretin as a potential therapeutic treatment for autistic patients urges a better understanding of the neuroactive functions of secretin. Indeed, there is an increasing body of evidence pointing to the direction that, in addition to other peptides in the secretin/glucagon superfamily, secretin is also a neuropeptide. The purpose of this review is to discuss the recent data for suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…In WT mice, SCT was strongly expressed in the soma and dendrites of Purkinje cells (Figures 1b and d), consistent with results obtained from a previous rat cerebellum study (Yung et al, 2001). In Pur-Sct À / À mice, SCT was still expressed in the deep cerebellar nuclei, hippocampus, and hypothalamus (Figures 1f-i) as previously described (Ng et al, 2002), confirming the Purkinjespecific knockout of SCT. The wide distribution of SCT in the central nervous system indicates its multiple central functions, some of which have been demonstrated by our research group, including water homeostasis (Chu et al, 2009;Lee et al, 2010) and food intake (Cheng et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In WT mice, SCT was strongly expressed in the soma and dendrites of Purkinje cells (Figures 1b and d), consistent with results obtained from a previous rat cerebellum study (Yung et al, 2001). In Pur-Sct À / À mice, SCT was still expressed in the deep cerebellar nuclei, hippocampus, and hypothalamus (Figures 1f-i) as previously described (Ng et al, 2002), confirming the Purkinjespecific knockout of SCT. The wide distribution of SCT in the central nervous system indicates its multiple central functions, some of which have been demonstrated by our research group, including water homeostasis (Chu et al, 2009;Lee et al, 2010) and food intake (Cheng et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the SCT immunoreactivity found in rat and pig brain extracts (O'Donohue et al, 1981), the expression of SCT and its receptor (SCTR) have also been detected in various brain regions, including the cortex, hippocampus, hypothalamus, and brainstem (Ng et al, 2002) across multiple developmental stages (Siu et al, 2005(Siu et al, , 2006, leading to the hypothesis of a putative neuropeptide role for SCT. Our research group previously used SCT and SCTR knockout mouse models to demonstrate the endogenous release of SCT in the hypothalamus (Chu et al, 2006) and examine related central mechanisms in the regulation of water homeostasis (Chu et al, 2007;Chu et al, 2009;Lee et al, 2010) and food intake (Cheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Secretin as a member of the secretin/glucagon family Secretin is a member of the secretin/glucagon superfamily which includes a pleiotropic group of brain-gut peptides that share significant structural and conformational homology, with affinity for the secretin/glucagon receptor superfamily of the secretin G protein-coupled receptor (GPCR) family (Ng et al 2002, Siu et al 2006, Cardoso et al 2010. Both sequence and secondary structure of the secretin/glucagon superfamily peptides are highly conserved, in which the latter consists of a random N-terminal structure and a C-terminal alpha helix (Wray et al 1998, Bourgault et al 2009).…”
Section: Structural Evolution Of Secretinmentioning
confidence: 99%
“…Since secretin is a member of the family of brain-gut peptides, perhaps it also acts as a neuropeptide, signaling centers in the brain [Ng et al, 2002;. A landmark study by Nelson and colleagues [2001] demonstrated differences in levels of VIP, a regulatory molecule in brain development, in neonatal blood of children with autism.…”
Section: Secretinmentioning
confidence: 99%